2020
DOI: 10.1111/oik.07274
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization drives an early spring for plants but not for pollinators

Abstract: Urbanization is one of the major threats to wild plants and pollinators, and its global increase demands a better understanding of the mechanism driving its negative impact. Urban warming and altered local environmental conditions have the potential to affect the timing of flowering and of pollinator activity. While previous evidence has shown that plant phenology tends to advance in urban areas, little is known about its effects on pollinator phenology. In this study we simultaneously assessed the response of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 81 publications
(96 reference statements)
1
41
0
Order By: Relevance
“…Microclimates, or local climatic conditions within habitats, can vary across urban environments and even within individual habitat patches depending on the biotic and abiotic qualities of a space [ 13 , 74 , 75 ]. Vegetation type and cover along with background environmental warming are two such characteristics that can influence local microclimate [ 76 ].…”
Section: Local Featuresmentioning
confidence: 99%
“…Microclimates, or local climatic conditions within habitats, can vary across urban environments and even within individual habitat patches depending on the biotic and abiotic qualities of a space [ 13 , 74 , 75 ]. Vegetation type and cover along with background environmental warming are two such characteristics that can influence local microclimate [ 76 ].…”
Section: Local Featuresmentioning
confidence: 99%
“…The cascading effects of this asynchrony on plantanimal interactions are largely uncharacterized. In a rare example along these lines, Fisogni et al (2020) recently observed that urbanization advanced the timing of flowering in France, but not pollinator flight, potentially leading to disrupted pollination in cities. In another example, ecological theory predicts that higher trophic levels may become less synchronized due to the urban heat island effect, disrupting ecosystem services, such as biological pest control.…”
Section: Synchrony/asynchrony Time Lags and Delaysmentioning
confidence: 99%
“…Less is known about insects' phenological response to urbanization. The emergence of some insect species appears to be advancing in urbanized areas (Diamond et al, 2015;Chick et al, 2019), but other studies have found no change in phenology across urbanization gradients, despite phenological advances in co-occurring plant species (Seress et al, 2018;Fisogni et al, 2020). The interaction between urbanization and regional temperature can be an important driver of spatial phenology patterns, as urbanization appears to advance plant phenology in cold areas but causes delays in warm areas (Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%